Methane-Derived Carbon in the Benthic Food Web in Stream Impoundments - Mbaka, John Gichimu; Mbaka, John Gichimu; Somlai, Celia; Ko¨pfer, Denis; Maeck, Andreas; Lorke, Andreas; Scha¨fer, Ralf B. (Public Library of Science, 2014)
Methane gas (CH4) has been identified as an important alternative source of carbon and energy in some freshwater food webs. CH4 is oxidized by methane oxidizing bacteria (MOB), and subsequently utilized by chironomid larvae, which may exhibit low d13C values. This has been shown for chironomid larvae collected from lakes, streams and backwater pools. However, the relationship between CH4 concentrations and d13C values of chironomid larvae for in-stream impoundments is unknown. CH4 concentrations were measured in eleven in-stream impoundments located in the Queich River catchment area, South-western Germany. Furthermore, the d13C values of two subfamilies of chironomid larvae (i.e. Chironomini and Tanypodinae) were determined and correlated with CH4 concentrations. Chironomini larvae had lower mean d13C values (2 29.2 to 225.5 %), than Tanypodinae larvae (226.9 to 225.3 %). No significant relationships were established between CH4 concentrations and d13C values of chironomids (p.0.05). Mean d13C values of chironomid larvae (mean: 226.8%, range: 2 29.2% to 225.3%) were similar to those of sedimentary organic matter (SOM) (mean: 228.4%, range: 229.3% to 227.1%) and tree leaf litter (mean: 229.8 %, range: 230.5% to 229.1%). We suggest that CH4 concentration has limited influence on the benthic food web in stream impoundments.